FAP imaging in rare cancer entities: first clinical experience in a broad spectrum of malignancies - Dendl, Katharina; Finck, Rebecca; Giesel, Frederik L.; Kratochwil, Clemens; Lindner, Thomas; Mier, Walter; Cardinale, Jens; Kesch, Claudia; Röhrich, Manuel; Rathke, Hendrik; Gampp, Heike; Ristau, Jonas; et al. (European journal of nuclear medicine and molecular imaging, 2022)
68 Ga-FAPI (fibroblast activation protein inhibitor) is a rapidly evolving and highly promising radiotracer for PET/CT imaging, presenting excellent results in a variety of tumor entities, particularly in epithelial carcinomas. This retrospective analysis sought to evaluate the potential and impact of FAPI-PET/CT in rare cancer diseases with respect to improvement in staging and therapy, based on tracer uptake in normal organs and tumors.
Online veröffentlicht: 03. August 2021
Gesehen am 26.01.2023